An interdisciplinary multimodal integrative healthcare program for depressive and anxiety disorders - Wijnen, Jaap; Gordon, Nicole Louise; van 't Hullenaar, Geert; Pont, Marc Lucas; Geijselaers, Marciano Wilhelmina Henricus; Van Oosterwijck, Jessica; de Jong, Jeroen (Frontiers in Psychiatry, 2023)
Objective: Although multimodal interventions are recommended in patients with severe depressive- and/or anxiety disorders, available evidence is scarce. Therefore, the current study evaluates the effectiveness of an outpatient secondary care interdisciplinary multimodal integrative healthcare program, delivered within a transdiagnostic framework, for patients with (comorbid) depressive- or/and anxiety disorders. Methods: Participants were 3900 patients diagnosed with a depressive- and/or anxiety disorder. The primary outcome was Health-Related Quality of Life (HRQoL) measured with the Research and Development-36 (RAND-36). Secondary outcomes included: 1) current psychological and physical symptoms measured with the Brief Symptom Inventory (BSI) and 2) symptoms of depression, anxiety, and stress measured with the Depression Anxiety Stress Scale (DASS). The healthcare program consisted of two active treatment phases: main 20-week program and a subsequent continuation-phase intervention (i.e. 12-month relapse prevention program). Mixed linear models were used to examine the effects of the healthcare program on primary/secondary outcomes over four time points: before start 20-week program (T0), halfway 20-week program (T1), end of 20-week program (T2) and end of 12-month relapse prevention program (T3). Results: Results showed significant improvements from T0 to T2 for the primary variable (i.e. RAND-36) and secondary variables (i.e. BSI/DASS). During the 12-month relapse prevention program, further significant improvements were mainly observed for secondary variables (i.e. BSI/DASS) and to a lesser extend for the primary variable (i.e. RAND-36). At the end of the relapse prevention program (i.e. T3), 63% of patients achieved remission of depressive symptoms (i.e. DASS depression score ≤ 9) and 67% of patients achieved remission of anxiety symptoms (i.e. DASS anxiety score ≤ 7). Conclusions: An interdisciplinary multimodal integrative healthcare program, delivered within a transdiagnostic framework, seems effective for patients suffering from depressive- or/and anxiety disorders with regard to HRQoL and symptoms of psychopathology. As reimbursement and funding for interdisciplinary multimodal interventions in this patient group has been under pressure in recent years, this study could add important evidence by reporting on routinely collected outcome data from a large patient group. Future studies should further investigate the long-term stability of treatment outcomes after interdisciplinary multimodal interventions for patients suffering from depression and/or anxiety disorders.